Thinking straight queer imaging in Lino Brocka's Maynila (1975) - David, Joel (2012)
The separation in so-called public political discourse and private identity issues attained recent cultural cutting-edge status in the articulation of gender issues. In view of the artificiality of disciplinary boundaries, this paper seeks to evaluate the potential of queer politics (focused on gay-male practice) within the exploratory terms provided by a major city film, Lino Brocka's Maynila : Sa mga kuko ng liwanag (1975), produced during martial rule. The area of application of this analysis will be Philippine popular culture, in consideration of the country's position as a post-colonized territory that had set up a dictatorial regime to facilitate neocolonial control by the US.